Daniel Templon 1978-1983. (1983)
Alberola, Jean-Michel ; Andre, Carl ; Appel, Karel ; Beckley, Bill ; Bioulès, Vincent ; Cane, Louis ; César ; Chia, Sandro ; Clemente, Francesco ; Connel, Kim Mc ; Cucchi, Enzo ; Davis, Brad ; Debré, Olivier ; Riverhead (New York) ; Gac, Jean Le ; Giorda, Patrice ; Immendorff, Jörg ; Jenney, Neil ; Judd, Donald ; Klossowski, Pierre ; Kushner, Robert ; Lichtenstein, Roy ; De Maria, Nicola ; Martinez, Jacques ; Morris, Robert ; Newton, Helmut ; Oldenburg, Claes ; Olitski, Jules ; Paladino, Mimmo ; Poirier, Anne & Patrick ; Rauschenberg, Robert ; Ripps, Rodney ; Rosenquist, James ; Rothenberg, Susan ; Schnabel, Julian ; Segal, George ; Smyth, Ned ; Stella, Frank ; Thiolat, Dominique ; Ben ; Venet, Bernar ; Warhol, Andy ; Wesselman, Tom ; Zakanitch, Robert
Frans
boek